Exploring educators’ challenges of online learning in Covid-19 at a rural school, South Africa - Mukana, K.; Aloka, P.J.O (My University, 2020)
Abstract. This study explored the perceived challenges of online learning encounter by rural educators in response to COVID-19 pandemic at a selected rural school in South Africa. Within the qualitative approach, a multiple case study was used as a research design. A sample size of six participants (N=6, two males and four females) was drawn from a rural school in a Thabo Mofutsanyana District in the Free State Province. Purposive and convenience sampling techniques were used to select participants in this study. The participants had teaching experience ranging from 2 to 7 years. Data were collected through telephone interviews and analysed using thematic analysis. The finding suggested that the Protection Motivation Theory was an insightful framework in responding to the challenges emanating from COVID-19 induced online teaching and learning. Thus, the study revealed that there are various challenges to online learning. These include poor parental involvement in children’s homework, incomplete work and poor performance, insufficient personal protective equipment, poor access to network access, and lack of learning devices. Subsequently, we recommend that stakeholders such as the Department of Education, Department of Basic Education, and School Governing Bodies, among others, should ensure that parents are sensitized about the need for learners to manage the resources at their disposal. Furthermore, the provision of adequate resources such as; Internet connectivity and Information and Communication Technologies learning devices is imperative. Keywords: Online learning; COVID-19; Protection Motivation Theory; Rural school; Educators’ challenges